PENGARUH INOVASI PRODUK DAN CUSTOMER EXPERIENCE TERHADAP LOYALITAS NASABAH DENGAN VARIABEL MEDIASI KEPUASAN NASABAH GEN Z PADA BANK DIGITAL (SEABANK) DI KOTA MANADO - Putri Dewi Sartika, Putri Dewi Sartika; Lumanauw, Bode; Soepeno , Djurwati (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The development of digital technology is driving the transformation of banking services, making product innovation and customer experience key to creating satisfaction and loyalty, especially for Generation Z who are digitally oriented and easy to switch services. This study aims to analyze the effect of product innovation and customer experience on customer loyalty, with customer satisfaction as a mediating variable, among Generation Z users of SeaBank in Manado City. This study employed a quantitative research approach using a survey method. The population consisted of Generation Z customers who actively use the SeaBank digital banking application in Manado City, with a total sample of 100 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with the assistance of SmartPLS software. The results indicate that product innovation and customer experience have a positive and significant effect on customer satisfaction.